Effects of Chinese Liquors on Cardiovascular Disease Risk Factors in Healthy Young Humans - Ju-Sheng Zheng; Jing Yang; Tao Huang; Xiao-Jie Hu; Ming Luo; Duo Li (The Scientific World Journal)
Objectives. To elucidate whether consumption of two Chinese liquors, tea-flavor liquor (TFL) and traditional Chinese liquor (TCL) have protective effects on cardiovascular disease (CVD) risk factors in healthy human subjects. Methods. Forty-five healthy subjects (23 men, 22 women), aged 23–28, were recruited and randomized into two groups: TFL and TCL, and consumed 30 mL/day (45% (v/v) alcohol) of either liquor for 28 days. Results. Serum high-density lipoprotein cholesterol/low-density lipoprotein cholesterol (HDL-C/LDL-C) and apolipoprotein A1 were significantly increased, and total cholesterol (TC) and TC/HDL-C were significantly decreased after the intervention in both groups (P<0.05). Serum uric acid (P=0.004 for TFL, P=0.001 for TCL), glucose (P<0.001 for TFL, P<0.001 for TCL) and endothelial adhesion molecules (P<0.05) were significantly decreased after the intervention. ADP-induced whole blood platelet aggregation was also significantly decreased after the intervention in both TFL and TCL groups (P<0.05). Conclusions. TFL and TCL consumption had protective effects on CVD risk factors in young humans. However, the results were valid only for 28 days, and that the possibility of adverse effect (liver, kidney) of chronic alcohol consumption should be considered.